Evaluation of environmental impacts and GHG of palm polyol production using life cycle assessment approach - Zolkarnain, N.; Yusoff, S.; Subramaniam, V.; Maurad, Z.A.; Abu Bakar, Z.; Ghazali, R.; Abu Hassan, H. (Lembaga Minyak Sawit Malaysia, 2015)
Presently, very few life cycle assessment (LCA) studies have been conducted and reported on the production of palm polyol. Previously, most of the LCA studies on the polyol production are limited to petroleum, soya or castor polyol. In this study, a LCA of a palm polyol was performed. The objective of this study is to identify any potential environmental impacts that could be associated with the production of palm polyol. The cradle-to-gate system boundary for the production of palm polyol shows that the most significant impact from the palm polyol production comes from the energy use at the polyol plant. This impact is mainly contributed by electricity, and production of hydrogen peroxide and formic acid that were used during the epoxidation process. The largest greenhouse gasses (GHG) contribution was from consumption of electricity from the national grid that was mainly used for pilot plant polyol process. However, from this study, about 29% reduction in the GHG emissions generated by the production of palm polyol could be achieved by using the best approach normally used in oil palm industry which is using continued land use and biogas capture scenario.